Ablation of angiotensin type 2 receptor prevents endothelial nitric oxide synthase glutathionylation and nitration in ischaemic abductor muscle of diabetic mice. (January 2020) - Robillard, Stéphanie; Mercier, Clément; Breton, Valérie; Paquin-Veillette, Judith; Guay, Andréanne; Lizotte, Farah; Geraldes, Pedro
Peripheral artery disease is a severe complication of diabetes. We have reported that the deletion of angiotensin type 2 receptor in diabetic mice promoted vascular angiogenesis in the ischaemic muscle 4 weeks following ischaemia. However, the angiotensin type 2 receptor deletion beneficial effects occurred 2 weeks post surgery suggesting that angiotensin type 2 receptor may regulate other pro-angiogenic signalling pathways during the early phases of ischaemia. Nondiabetic and diabetic angiotensin type 2 receptor–deficient mice ( Agtr2 −/Y ) underwent femoral artery ligation after 2 months of diabetes. Blood perfusion was measured every week up to 2 weeks post surgery. Expression of vascular endothelial growth factor, vascular endothelial growth factor receptor and endothelial nitric oxide synthase expression and activity were evaluated. Blood flow reperfusion in the ischaemic muscle of diabetic Agtr2 +/Y mice was recovered at 35% as compared to a 68% recovery in diabetic Agtr2 −/Y mice. The expression of vascular endothelial growth factor and its receptors was diminished in diabetic Agtr2 +/Y mice, an observation not seen in diabetic Agtr2 −/Y mice. Interestingly, Agtr2 −/Y mice were protected from diabetes-induced glutathionylation, nitration and decreased endothelial nitric oxide synthase expression, which correlated with reduced endothelial cell death and enhanced vascular density in diabetic ischaemic muscle. In conclusion, our results suggest that the deletion of angiotensin type 2 receptor promotes blood flow reperfusion in diabetes by favouring endothelial cell survival and function.